Stanisław Judycki’s Philosophy of Metaphysical Optimism - Łukasiewicz, Dariusz (Roczniki Filozoficzne, 2024)
In the article, I discuss the main premises of metaphysical optimism present in the philosophy of Stanisław Judycki. These include: the causa totalis argument for the existence of a supreme being, which I call the modal argument, the argument for the personal nature of the supreme being, arguments for the perfect goodness of the supreme being, and universalistic (inclusive) eschatology. I consider all these metaphysical premises to be fundamentally accurate. I understand God’s omnipotence differently, more strongly than Stanisław Judycki. All God’s attributes are including within the reach of God’s omnipotent will embracing perfect goodness, which was expressed by God’s actions such as the Incarnation and destruction of all evil.